2019
DOI: 10.1021/acscatal.8b04943
|View full text |Cite
|
Sign up to set email alerts
|

Flowerlike Ag-Supported Ce-Doped Mn3O4 Nanosheet Heterostructure for a Highly Efficient Oxygen Reduction Reaction: Roles of Metal Oxides in Ag Surface States

Abstract: Tuning Ag surface states by metal oxides is a feasible method to enhance the oxygen reduction reaction (ORR) performance of Ag-based catalysts. Herein, we develop a heterostructural electrocatalyst of flowerlike Ag-supported nanosheets of metal oxides (Mn 3 O 4 and Ce-doped Mn 3 O 4 ) by a facile two-step solution method for a highly efficient alkaline ORR. Not only does Mn 3 O 4 /Ag exhibit activity comparable to that of commercial Pt/C but also small amounts of Ce 3+ (2−5 mol %) doped into Mn 3 O 4 make the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 58 publications
2
51
0
Order By: Relevance
“…The ORR polarization curves achieved at different rotating speeds were illustrated in Figure 3a (PN-NCNT) and Figure S1a-d (PN-CNT, NCNT, N 3 − /NCNT, and CNT). As expected, current density increased with the electrode rotating speed increase, which can be attributed to the enhanced diffusion of electrolytes [47,48].…”
Section: Resultssupporting
confidence: 76%
“…The ORR polarization curves achieved at different rotating speeds were illustrated in Figure 3a (PN-NCNT) and Figure S1a-d (PN-CNT, NCNT, N 3 − /NCNT, and CNT). As expected, current density increased with the electrode rotating speed increase, which can be attributed to the enhanced diffusion of electrolytes [47,48].…”
Section: Resultssupporting
confidence: 76%
“…However, the intrinsic ORR and OER activities of Mn 3 O 4 are still unsatisfactory because of its low electrical conductivity and unoptimized electronic structure [16,17]. To solve these issues, considerable efforts, including size modulation [18], the formation of mixed metal oxides [19][20][21], doping with other transition metals [22][23][24][25][26], and hybridization with conductive substrates [17,27,28], have been undertaken to enhance both the OER and ORR activities of pristine Mn 3 O 4 . For instance, Chen and coworkers reported that a mixed-metal oxide, Co x Mn 3-x O 4 , possessed an ORR performance similar to that of the counterpart Pt/C catalyst and proper OER activity, in which the Co/Mn composition and surface valence value were found to affect the extent of oxygen activation [22].…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al. further studied metal doping on the ORR activity of Ag/Mn 3 O 4 [45] . They considered Ce, Fe, Co, Ni, and Cu doping of Mn 3 O 4 and found that the doping of Ce into Mn 3 O 4 can elevate the ORR activity of Ag/Mn 3 O 4 higher than Pt/C in 0.1 M KOH (Figure 4d).…”
Section: Interface Engineering For Orr and Oermentioning
confidence: 99%